Investigation on diagnosis and metabolic profile of ovarian cysts in dairy cows - Nora MIMOUNE; Rachid KAIDI; Mohamed Yassine AZZOUZ; Safia ZENIA; Mohamed Hocine BENAISSA; Gary ENGLAND (Kafkas Universitesi Veteriner Fakültesi Dergisi, 2017)
A clinical study was performed to evaluate the diagnostic methods for ovarian cysts (OC), and to determine the metabolic profiles of animals with OC in the region of Mitidja in the North of Algeria. A total of 504 non-pregnant lactating cows were used in this study. Ultrasonography was performed by EXAGO scanner and was combined with assessment of serum P4. Biochemical serum parameters were assayed by spectrophotometry and insulin and cortisol serum measurement was performed by electrochemiluminescence. The results showed an overall incidence of 11.9% of OC. The incidence of OC was higher among cows in third lactation. Holstein breed was the most affected by OC compared with other breeds (P<0.001). There were no effects of average BCS (Body Condition Scoring) and milk production on the incidence of OC (P>0.05). OC were single in 91% of cases. They were found mainly on the right ovary (66.66%). Seasonality had a significant influence on incidence rate of OC with higher incidence rates during winter and spring (71.66%); while, 28.33% of OC were detected during the summer and autumn (P<0.05). OC were associated with low serum concentrations of glucose, insulin and urea as well as high levels of cortisol. Ultrasound examination and progesterone assays were proposed as the most effective diagnostic combination to diagnose OC. In conclusion, in addition to hormonal imbalances, metabolic disorders are involved in the formation and/or persistence of OC. Therefore, the use of metabolic indicators in understanding and exploration of OC is of great interest.